NATURAL DISTRIBUTION AND ALKAMIDES PRODUCTION IN ACMELLARADICANS - Ramírez-Chávez, E.; Molina-Torres , J.; Ríos-Chávez, P. (Emirates Journal of Food and Agriculture, 2011)
Alkamides comprise over 200 related compounds. There are many studies revealing much useful information about the structure, chemistry and biological activity of this novel class of compounds. However, there is a lack of information about the natural distribution and their synthesis. Here we reported the synthesis of the main alkamides during the growth of Acmella radicans. A. radicans seed were surface-sterilized and sowed in soil. One week after placement in the soil, the seed began germination with 90% of germination. Alkamide content was evaluated every week during six months. We found six alkamides in this plant. N-isobutyl-(2E,6Z,8E)- decatrienamide (affinin) biosynthesis initiated, just before seedling. In the third week appeared the N-(2-methylbutyl) -(2E,6Z,8E)-decatrienamide and the N-(2-methylbutyl)- (2E,4Z,8E,10E)- dodecatetraenamide; N-(2-phenylethyl)- (2Z,4E)-octadienamide; N-(2-phenylethyl)-nona-2E-ene- 6,8-diynamide and 3-pheny-N-(2-phenylethyl)-2-propenamide appeared in the fifth week. The profiles of these six alkamides in A. radicans vary with the time and developmental stage. Affinin and other alkamides have been found to alter the architecture of the root system and to regulate cell division and differentiation process in Arabidopsis thaliana. The dependence of the alkamides concentration with plant age, found in this study suggests a possible plant hormones role of the alkamides in this plant.